OPTIMAL PID CONTROLLER BASED ON AN IMPROVED SPARROW SEARCH ALGORITHM FOR MULTI-AREA FREQUENCY CONTROL - Amobi Edward OKOLO; Elvis TWUMASI; Emmanuel Asuming FRIMPONG (Carpathian Journal of Electrical Engineering, 2023)
To boost power system reliability there must be a good scheme for the automatic generation control to maintain the generation-load balance. The development of this scheme started with the enhancement of the sparrow search algorithm, where the initial population and producer selection was targeted to improve the search quality. The enhancement made was used to optimize the gain parameters of the PID controller increasing the overall system performance. The proposed scheme was tested on the two-area power system in the MATLAB/Simulink environment and comparisons were made with recent publications. Integral time absolute error (ITAE) was used as the performance index. The proposed method shows improved performance with minimum settling time. This work presents the enhancement of the sparrow search algorithm for the automatic generation control of a two-area non-reheat thermal power system.